Voluntary and Non-Voluntary Blood Donations Employees at Sentosa Mother and Child Hospital Makassar - Lao, Jemmy; Niartiningsih, Andi (International Journal Papier Advance and Scientific Review, 2023)
The goal of this study is to determine whether or not the staff of Sentosa Mother and Child Hospital in Makassar voluntarily donate blood. Sentosa Mother and Child Hospital in Makassar hosted this study. This study used a number of different research strategies. 53 participants make up the sample size for this study. According to the results of this research, According to the data, a total of 48 respondents rated their level of awareness as excellent, while 50 respondents rated their level of knowledge as excellent, and 51 respondents rated their level of understanding of the reasons why people do not donate as excellent. Research The majority of adults are well-informed, have positive views about blood donation, and regularly give blood on their own will. Lack of nursing during pregnancy, advanced age, sickness, and lack of free time are among reasons why people do not give blood. There is also a statistically significant relationship between gender and attitude level and blood donation behavior in this research. Local, national, and transfusion organizations need to implement measures to improve the education of individuals and inspire them to voluntarily provide blood. The study’s findings on what makes people more or less likely to give blood are timely in light of the current epidemic. We need to address them to increase blood donations in this scenario.